Expérience d´intégration de la santé mentale en première ligne de soins en Guinée - Sow, Abdoulaye (Pan Afr Med J, 2020)
INTRODUCTION: the low coverage of specialized mental health services and the shortage of human resources for mental health are enormous challenges for the health care system in Africa. The integration of mental health support into primary health care is a substantial and feasible complementary intervention to specialized services. We collected and analyzed data from 5 Health Care Centers (HCC) that had integrated this care package in Guinea. METHODS: we conducted a descriptive study of new cases of mental health issues between 2012 and 2017. The reasons for consultations and diagnoses were identified and analyzed on the basis of consultation registries and individual medical records. RESULTS: a total of 4.995 patients with mental health problems received consultations (2.8% of general consultations; 0.5 -7.7% according to the centers). The average age of patients was 27,9 years (± 16.1). The most common reasons for consultations were: insomnia 44.4% (n = 2081), seizures 39% (n = 1827), behavioral disorders 31.9% (n = 1263) and hallucinations 26.1% (n = 1224). The most common diagnoses were: epilepsy 36.8% (n = 1773) and psychotic disorders 33.5% (n = 1613). Eighty eight point four per cent (n = 4418) of patients received medical treatment, most often combined with psychological support. CONCLUSION: this study highlights that in the Guinean context, where access to specialized mental health care is very limited, patients with mental ill, even with severe medical conditions, can be followed up in the health centers by non-specialized but trained mental health professionals.